Laurel leaf extracts for honeybee pest and disease management: Antimicrobial, microsporicidal, and acaricidal activity - Damiani, Natalia (2014)
A diverse set of parasites and pathogens affects productivity and survival of Apis mellifera honeybees. In beekeeping, traditional control by antibiotics and molecules of synthesis has caused problems with contamination and resistant pathogens. In this research, different Laurus nobilis extracts are tested against the main honeybee pests through an integrated point of view. In vivo effects on bee survival are also evaluated. The ethanol extract showed minimal inhibitory concentration (MIC) values of 208 to 416 μg/mL, having the best antimicrobial effect on Paenibacillus larvae among all substances tested. Similarly, this leaf extract showed a significant antiparasitic activity on Varroa destructor, killing 50 % of mites 24 h after a 30-s exposure, and on Nosema ceranae, inhibiting the spore development in the midgut of adult bees ingesting 1 × 104 μg/mL of extract solution. Both ethanol extract and volatile extracts (essential oil, hydrolate, and its main component) did not cause lethal effects on adult honeybees. Thus, the absence of topical and oral toxicity of the ethanol extract on bees and the strong antimicrobial, microsporicidal, and miticidal effects registered in this study place this laurel extract as a promising integrated treatment of bee diseases and stimulates the search for other bioactive phytochemicals from plants.